2004
DOI: 10.1038/nature02385
|View full text |Cite
|
Sign up to set email alerts
|

Bmi1 is essential for cerebellar development and is overexpressed in human medulloblastomas

Abstract: Overexpression of the polycomb group gene Bmi1 promotes cell proliferation and induces leukaemia through repression of Cdkn2a (also known as ink4a/Arf) tumour suppressors. Conversely, loss of Bmi1 leads to haematological defects and severe progressive neurological abnormalities in which de-repression of the ink4a/Arf locus is critically implicated. Here, we show that Bmi1 is strongly expressed in proliferating cerebellar precursor cells in mice and humans. Using Bmi1-null mice we demonstrate a crucial role for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
424
1
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 495 publications
(439 citation statements)
references
References 23 publications
13
424
1
1
Order By: Relevance
“…This finding also demonstrates that HH-GLI signaling can upregulate the PDGF-C ligand in addition to its receptor, PDGFR-a (Xie et al, 2001). This also shows that BMI-1 is regulated by aberrant HH-GLI signaling in NIH3T3, as has been observed in the background of cerebellar development and medulloblastoma (Leung et al, 2004). Even though GLI1 signaling is important to the EWS/FLI1-transformed Figure 3 EWS/FLI1 enhancement of GLI1 signaling is HH independent.…”
Section: Ews/fli1 Deregulates Gli1supporting
confidence: 70%
See 1 more Smart Citation
“…This finding also demonstrates that HH-GLI signaling can upregulate the PDGF-C ligand in addition to its receptor, PDGFR-a (Xie et al, 2001). This also shows that BMI-1 is regulated by aberrant HH-GLI signaling in NIH3T3, as has been observed in the background of cerebellar development and medulloblastoma (Leung et al, 2004). Even though GLI1 signaling is important to the EWS/FLI1-transformed Figure 3 EWS/FLI1 enhancement of GLI1 signaling is HH independent.…”
Section: Ews/fli1 Deregulates Gli1supporting
confidence: 70%
“…Figure 4a shows, that as in these other systems, EWS/FLI1 does lead to upregulation of cMYC in NIH3T3. As the polycomb gene BMI-1 has been shown to be targeted by both HH signaling (Leung et al, 2004) and cMYC (Guney et al, 2006), we assessed its expression and found that like PATCHED1 and PDGF-C it is an HH-GLI1 target which is also deregulated by EWS/ FLI1 in NIH3T3.…”
Section: Ews/fli1 Deregulates Gli1mentioning
confidence: 99%
“…The gene, Bmi-1 , was initially shown to regulate haematopoiesis and differentiation of lymphocytes [25] and to be involved in cerebral development [26]. To date, the proto-oncogene Bmi-1 has been reported to be up-regulated in a large number of neoplasias, namely in lymphomas [27], cerebral tumours [26], breast cancer [13] and other epithelial tumours [28,29] and to be an oncogene associated with poor prognosis in various tumours [12].…”
Section: Discussionmentioning
confidence: 99%
“…To date, the proto-oncogene Bmi-1 has been reported to be up-regulated in a large number of neoplasias, namely in lymphomas [27], cerebral tumours [26], breast cancer [13] and other epithelial tumours [28,29] and to be an oncogene associated with poor prognosis in various tumours [12]. To investigate whether or not the abnormal expression of Bmi-1 is involved in the pathogenesis of ovarian carcinoma, in the present study, the protein expression of Bmi-1 was examined firstly by IHC in normal ovaries, benign and borderline epithelial ovarian tumors, and malignant epithelial cancers.…”
Section: Discussionmentioning
confidence: 99%
“…2,4 Of note, it has been demonstrated that Bmi1 is necessary for the maintenance of not only leukemic stem cells but also cancer stem cells in solid tumors. 5,6 Considering that high expression levels of Bmi1 are reported in a wide range of malignancies, Bmi1 could be a general regulator of cancer stem cells as in normal stem cells.…”
mentioning
confidence: 99%